1974
DOI: 10.1002/1097-0142(197407)34:1<54::aid-cncr2820340109>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Biological characterization of a high energy neutron beam for radiation therapy

Abstract: In anticipation of the use of the Naval Research Laboratory (NRL) 35‐MeV neutron facility for radiotherapy by the Middle Atlantic Neutron Therapy Association (MANTA), RBE values were obtained for a diversity of biological end points. Animals were exposed to neutrons at a dose‐rate of approximately 60 rads/min, in Lucite exposure chambers which also served as scattering material. Parallel experiments were performed, using the same exposure apparatus, in which animals were exposed to 60Co gamma rays given at app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1975
1975
1979
1979

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The animals were irradiated in a Lucite wheel described previously (Wilson and Montour 1973) under conditions used in all other r .b .e . studies reported by Montour, Wilson, Rogers, Theus and Attix 1974 . With the testes upstream in the radiation beam throughout the exposure, doses to each animal's midpoint were approximately 18 per cent less than to the testes .…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…The animals were irradiated in a Lucite wheel described previously (Wilson and Montour 1973) under conditions used in all other r .b .e . studies reported by Montour, Wilson, Rogers, Theus and Attix 1974 . With the testes upstream in the radiation beam throughout the exposure, doses to each animal's midpoint were approximately 18 per cent less than to the testes .…”
Section: Methodsmentioning
confidence: 86%
“…We have found each of two components in the mouse spleen and in the mouse thymus to be linear for both gamma rays and neutrons and, therefore, to have r .b .e . values unchanged by dose (Montour, Wilson, Rogers, Theus and Attix 1974) . It would appear that the `dual action' theory is useful in describing the radiation response of cell systems in which the survival curves have a shoulder, that is, systems in which cells accumulatè sublethal damage' following low LET radiation, but does not provide any insight into the mechanisms which result in greater cell killing with neutrons in systems which respond linearly to gamma rays or X-rays .…”
Section: Discussionmentioning
confidence: 93%